The Monkeys and Parrots of Gold Rush-era California - Conrad, Cyler (Ethnobiology Letters, 2022)
As immigrant gold miners migrated en masse to San Francisco and northern California during the Gold Rush-era (ca. 1849–1855), they experienced new animals. Stopping in ports throughout Central and South America, these argonauts saw, felt, smelled, heard, and occasionally consumed, mammals, birds, reptiles, and many more creatures, which were wholly exotic to those species found at home. Two types of animals that the Gold Rush populace encountered during this era include parrots and monkeys. Although found throughout tropical environments in areas far distant from northern California, these animals became quickly imported to San Francisco during the early 1850s. A wild, turbulent Gold Rush-era helped facilitate the importation of these exotic animal types, both for comfort and entertainment, as they helped provide a source of companionship for miners unaccustomed to the shock of 1850s northern California.